Utilisation des charges maximales et cumulatives sur la colonne vertébrale pour évaluer les emplois, la rotation des emplois et les contrôles techniques - Mardon Frazer (Perspectives Interdisciplinaires sur le Travail et la Santé)
Peak and cumulative forces on spinal structures have been identified as significant and statistically independent risk factors for reporting low back pain (LBP). This paper describes a software based approach which utilizes these risk factors to quantitatively predict the reporting of LBP by utilizing a Low Back Pain Reporting Index Score (LBPRI). Two automotive manufacturing jobs were assessed utilizing this approach and these results were utilized in the development of a specific administrative and engineering control. Analysis of the jobs with the controls in place indicated that the administrative control, job rotation, was less effective than assumed and produced an overall increase in the risk of reporting LBP. The engineering control resulted in an overall decrease in the risk of reporting LBP and this beneficial risk reduction would be delivered to any worker that performed this job. The results of this study indicate that both peak and cumulative loading must be considered in order to properly appreciate the risk of injury and the consequences associated with the implementation of administrative and engineering controls.